Trade Policy and Market Structure Interactions in Developing Countries. (IMF Working Papers; Working Paper ;, 1989)
This paper shows that the presence of quotas on imported inputs that are based on installed capacity can lead to capacity underutilization in manufacturing industries of developing countries. A replacement of such quotas, by tariffs leads to full capacity utilization under assumptions of both perfectly and imperfectly competitive markets. Furthermore, such a policy also eliminates strategic advantages for oligopolistic firms that arise in quota-based regimes.